The Importance of Aqidah Akhlak (Moral) in Building Noble Character - Nazhifah, aprilia Imroatun; Febryantika, Arlynda Engrasia; Munawir, H. (JUPE : Jurnal Pendidikan Mandala, 2023)
This article discusses the importance of strengthening the foundations of faith and building noble morals in individual and societal life. A strong foundation of faith provides certainty, stability and a clear view of the purpose of life, while noble character reflects behavior that is in accordance with religious and moral values. A strong foundation of faith is the basis for the development of good morals, while noble morals are concrete evidence of one's beliefs. Strengthening the foundations of faith and building noble morals provides benefits such as peace of mind, a strong personality, and a harmonious society. The method in this research is qualitative and literature study as data collection. This article provides an understanding of the importance of strengthening the foundations of faith and building noble morals in everyday life and how the two are interconnected and influence each other. By strengthening the foundations of faith and building noble morals, individuals can live their lives with integrity and provide benefits to themselves and the surrounding community.